2014
DOI: 10.1016/j.jpainsymman.2013.07.013
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Weekly Symptom Telemonitoring in Advanced Lung Cancer

Abstract: Context Lung cancer patients experience multiple, simultaneous symptoms related to their disease and treatment that impair functioning and health-related quality of life (HRQL). Computer technology can reduce barriers to nonsystematic, infrequent symptom assessment and potentially contribute to improved patient care. Objectives To evaluate the efficacy of technology-based symptom monitoring and reporting in reducing symptom burden in patients with advanced lung cancer. Methods This was a prospective, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
127
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(133 citation statements)
references
References 86 publications
5
127
0
1
Order By: Relevance
“…This was supplemented with extensive reference and citation searching, which allowed inclusion of articles published very recently. 41 The review team comprised a multiprofessional team of expert clinicians and researchers, and this aided the development of the review question, protocol, analysis, and synthesis of findings. Furthermore, our two-level review strategy allowed us to appraise the evidence from a general as well as specific perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was supplemented with extensive reference and citation searching, which allowed inclusion of articles published very recently. 41 The review team comprised a multiprofessional team of expert clinicians and researchers, and this aided the development of the review question, protocol, analysis, and synthesis of findings. Furthermore, our two-level review strategy allowed us to appraise the evidence from a general as well as specific perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Five articles 38,39,41,42,47 reported on acceptability to patients. The main findings were that patients found the intervention ''helpful in discussing important issues/telling professionals how they were feeling'' (weighted mean 69%) and that patients ''would use PCOMs feedback as part of standard care'' (weighted mean 88%).…”
Section: Acceptability and Feasibilitymentioning
confidence: 99%
“…Many studies have shown the feasibility of electronic capture and monitoring of patient-reported outcomes (PROs) for symptoms related to cancer treatment [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Most studies have focused on PRO capture at clinic visits with fewer studies evaluating automated systems developed for between-visit home monitoring and realtime follow-up for intensification of care for poorly controlled symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Authors have acknowledged the potential contribution that telehealth could play in palliative care for patients in rural and remote areas [15], the role that mobile technologies could play [16], and opportunities for specific population groups such as paediatrics [17] or lung cancer [18]. However, reviews and trials have also highlighted the need to build the evidence around palliative care telehealth in the community [1214, 19, 20].…”
Section: Introductionmentioning
confidence: 99%